Endocrine disruptors in sludge wastewater treatment plants: environmental complications - doi: 10.4025/actascitechnol.v35i2.10619 - Ferreira, Aldo Pacheco (Acta Scientiarum. Technology, 2012)
Concern over exposure to endocrine disruptors (EDs) and impacts on wildlife and human has gradually increased in importance in recent years. Wastewater systematically receives most if not all of these chemicals, so a deeper understanding of the fate of EDs in environment is sorely needed. We evaluated EDs concentration in the affluent and effluent from the Sludge Wastewater Treatment Plants (SWTPs) Penha and Ilha do Governador. It was used as evaluation parameter the determination of some target compounds, such as: alkylphenols, 17Î²-estradiol, bisphenol A; complementing with measures of physical and chemical parameters: temperature, pH, dissolved oxygen, total suspended solids, volatile suspended solids, and total chemical oxygen demand. Samples were collected along the line of treatment of each SWTP, and after laboratory procedures, analyzed by LC-MS/MS and ELISA techniques. In some samples, we verified concentrations of chemical compounds with potential to disrupt the endocrine system of living organisms. Therefore, the release of this effluent, even within the effluent discharge standards (BRASIL, 2005) or in condition to be purified by the water course, may lead to physiological changes in the organisms of the receptor water body. Â 